Development of UK guidance on the management of erectile dysfunction resulting from radical radiotherapy and androgen deprivation therapy for prostate cancer. Issue 1 (6th October 2014) - White, I. D.; Wilson, J.; Aslet, P.; Baxter, A. B.; Birtle, A.; Challacombe, B.; Coe, J.; Grover, L.; Payne, H.; Russell, S.; Sangar, V.; Van As, N.; et al.
Summary Aim To develop a management strategy (rehabilitation programme) for erectile dysfunction (ED) after radiotherapy (RT) or androgen deprivation therapy (ADT) for prostate cancer that is suitable for use in a UK NHS healthcare context. Methods PubMed literature searches of ED management in this patient group together with a survey of 28 experts in the management of treatment‐induced ED from across the UK were conducted. Results Data from 19 articles and completed questionnaires were collated. The findings discussed in this article confirm that RT/ADT for prostate cancer can significantly impair erectile function. While many men achieve erections through PDE5‐I use, others need combined management incorporating exercise and lifestyle modifications, psychosexual counselling and other erectile aids. This article offers a comprehensive treatment algorithm to manage patients with ED associated with RT/ADT. Conclusion Based on published research literature and survey analysis, recommendations are proposed for the standardisation of management strategies employed for ED after RT/ADT. In addition to implementing the algorithm, understanding the rationale for the type and timing of ED management strategies is crucial for clinicians, men and their partners.